Improvement of Mosque Financial Management (Case Study on Mosques in Tamansari Bandung Area) - Manggala Wijayanti, Intan; Rahmat Hidayat, Yayat; Rizki Febriadi, Sandy; Fawzi, Ramdhan; Hayfa Victoria, Salma (KnE Social Sciences, 2023)
The issue of financial management of mosque cash in Indonesia is varied. Each mosque in a certain area has a different financial management model with mosques in other areas, including in the Tamansari Village. The typological conditions that differ from one mosque to another are one of the factors that require special handling in certain mosques, in addition to the absence of simple bookkeeping in mosques in managing cash finances. Therefore, efforts are needed to improve the ability to manage mosque finances. This study aims to increase the understanding of DKM in managing mosque cash finances and skills in making simple mosque reports. The research object is 12 members of the DKM (Mosque Management Board) in the Tamansari area of Bandung. The data processing method used is a non-parametric test, namely the Wilcoxon method to test the difference between the average pretest and posttest. The results showed that the value of Asymp. Sig (2-tailed) of 0.002 < α of 0.05, thus a significant average difference was observed between the pretest and posttest. A negative rank value of 0 and a positive rank of 12 indicate that the posttest scores of all training participants are better than the pretest scores. Keywords: mosque financial management, mosque management, financial report